2021
DOI: 10.1101/2021.03.30.21254655
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 vaccine impact on rates of SARS-CoV-2 cases and post vaccination strain sequences among healthcare workers at an urban academic medical center: a prospective cohort study

Abstract: Background: COVID-19 vaccine trials and post-implementation data suggest vaccination decreases SARS-CoV-2 infections. Objective: Estimate COVID-19 vaccinations impact on SARS-CoV-2 case rates and viral diversity among healthcare workers (HCW) during a high community prevalence period. Design, Setting, Participants: A prospective cohort study from Boston Medical Center (BMC)s HCW vaccination program, where staff received two doses of BNT162b2 or mRNA-1273. Measurements: PCR-confirmed SARS-CoV-2 cases among HC… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 18 publications
(16 reference statements)
7
30
0
Order By: Relevance
“…All symptomatic cases were noted among partially vaccinated HCPs and were self-limiting with only 5 requiring hospitalization. Although our passive surveillance system was intended to capture the HCP vaccinated population who self-reported symptoms or who were exposed to a COVID-19 positive case, and not able to report true prevalence of infections (i.e., mild or asymptomatic infections may be missed), our findings are consistent with emerging reports of incident post-vaccination SARS-CoV-2 infections (15)(16)(17)(18). A recent multicenter prospective cohort study in England found vaccine effectiveness upwards of 85% (19).…”
supporting
confidence: 81%
“…All symptomatic cases were noted among partially vaccinated HCPs and were self-limiting with only 5 requiring hospitalization. Although our passive surveillance system was intended to capture the HCP vaccinated population who self-reported symptoms or who were exposed to a COVID-19 positive case, and not able to report true prevalence of infections (i.e., mild or asymptomatic infections may be missed), our findings are consistent with emerging reports of incident post-vaccination SARS-CoV-2 infections (15)(16)(17)(18). A recent multicenter prospective cohort study in England found vaccine effectiveness upwards of 85% (19).…”
supporting
confidence: 81%
“…The result corroborate the findings of similar studies done in other countries. 12,13 Interestingly, according to our analysis, these vaccines seem to be more protective in the younger age group rather than in older individuals. The reason for this discrepancy may be a result of sampling error.…”
Section: Discussionmentioning
confidence: 56%
“…A total of 33 studies were included in this review (Figure 1). Twenty-one were human studies (Table 2 and Table 3), [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]19,29,[36][37][38] and 12 were preclinical animal studies, with viral challenge 1-17 weeks post vaccination (Table 4). [20][21][22][39][40][41][42][43][44][45][46][47] In the previous report, a targeted literature search was conducted and 17 studies included.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Five of the human studies were randomized controlled trials, [4][5][6]18,19 eight were prospective cohort studies, 8,11 seven were retrospective cohort studies, 2,10,12,13,[36][37][38] and one was a case control study. 15 Figure…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation